2016
DOI: 10.2147/cia.s107675
|View full text |Cite
|
Sign up to set email alerts
|

BFH-OST, a new predictive screening tool for identifying osteoporosis in postmenopausal Han Chinese women

Abstract: PurposeTo develop a simple new clinical screening tool to identify primary osteoporosis by dual-energy X-ray absorptiometry (DXA) in postmenopausal women and to compare its validity with the Osteoporosis Self-Assessment Tool for Asians (OSTA) in a Han Chinese population.MethodsA cross-sectional study was conducted, enrolling 1,721 community-dwelling postmenopausal Han Chinese women. All the subjects completed a structured questionnaire and had their bone mineral density measured using DXA. Using logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…It was worth mentioning that the prevalence rate of OP in men was not related to age, which was different with previous studies about postmenopausal women. 11 , 26 , 30 Steuart et al designed a study that involved 518 elderly males to evaluate OST in identifying OP and found that an OST index of 6 or lower yielded the AUC of 0.67, a sensitivity of 82.6%, and a specificity of 33.6%, which was similar to this study. 31 OSTA was a screening tool for OP associated with age and weight, and this study suggested that age was a clinical risk factor of OP in elderly males according to worst hip criteria, whereas it had a limiting value in the WHO criteria.…”
Section: Discussionsupporting
confidence: 83%
“…It was worth mentioning that the prevalence rate of OP in men was not related to age, which was different with previous studies about postmenopausal women. 11 , 26 , 30 Steuart et al designed a study that involved 518 elderly males to evaluate OST in identifying OP and found that an OST index of 6 or lower yielded the AUC of 0.67, a sensitivity of 82.6%, and a specificity of 33.6%, which was similar to this study. 31 OSTA was a screening tool for OP associated with age and weight, and this study suggested that age was a clinical risk factor of OP in elderly males according to worst hip criteria, whereas it had a limiting value in the WHO criteria.…”
Section: Discussionsupporting
confidence: 83%
“…With the WHO criteria, the prevalence rates of osteopenia and osteoporosis among Han Beijing postmenopausal women were 48.8% and 28.4%, respectively, which was basically consistent with previously reported rates. 12,29 The high prevalence of OP emphasizes the need for a reliable and convenient screening tool to identify Chinese postmenopausal women at risk, because most OP patients are asymptomatic, making the diagnosis easy to be missed. Five different diagnostic criteria (WHO, lumbar spine, worst hip, femoral neck, and total hip criteria) were included in the present analysis, and comparisons were made among these different screening tools.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of asymptomatic OP (22.66%) and osteopenia (47.36%) among Chinese postmenopausal women were both high in a previous study. 12 Hence, identifying and prescreening OP is important to prioritize individuals at risk of OP for DXA scanning. Results obtained by using credible risk assessment tools could help clinicians decide whether further DXA examination is needed for patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this model [ 15 ], only weight and history of the previous fracture were selected in the ultimate model. The new model had been named the Beijing Friendship Hospital Osteoporosis Self-Assessment Tool for Elderly Male (BFH-OSTM) [ 20 ]. The model was calculated using the following formula: …”
Section: Methodsmentioning
confidence: 99%